2021
DOI: 10.1039/d1ra01504d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dispersion of metakaolin–graphene oxide hybrid in water and cement pore solution: can metakaolin really improve the dispersion of graphene oxide in the calcium-rich environment of hydrating cement matrix?

Abstract: The aggregation mechanism of an MK–GO hybrid in the pH range of 10–11 due to the surface complexation between Al(OH)4− formed by MK dissolution and the graphene layer of GO through Lewis acid–base interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In recent decades, nanotechnology as an alternative has attracted the attention of researchers for improving the properties of cementitious composites. The literature shows that the incorporation of nanoparticles, such as nano-TiO 2 , , carbon nanotube, and graphene oxide in cementitious composites can effectively enhance their brittle structure, microstructure, strength, and durability performance. For instance, it was reported that the flexural and compressive strengths of reactive powder concrete reinforced with nano SiO 2 -coated TiO 2 improved by 87% MPa and 12.26% MPa compared with the plain sample.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nanotechnology as an alternative has attracted the attention of researchers for improving the properties of cementitious composites. The literature shows that the incorporation of nanoparticles, such as nano-TiO 2 , , carbon nanotube, and graphene oxide in cementitious composites can effectively enhance their brittle structure, microstructure, strength, and durability performance. For instance, it was reported that the flexural and compressive strengths of reactive powder concrete reinforced with nano SiO 2 -coated TiO 2 improved by 87% MPa and 12.26% MPa compared with the plain sample.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of graphene oxide (GO) in cement mortar, an excess of oxygen functional groups in GO would trigger undesirable issues inside cement-based concrete. This is because both the negative charge of GO and the positive charge of Ca 2+ , Na + , and K + existing inside the cement matrix tend to agglomerate due to van der Waals forces [17]. The increased formation of agglomerates may result in the formation of a weak zone within the concrete matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although GO has benefits when mixed with cement, an excess of oxygen functional groups in GO can cause problems in the cement-based matrix. This is because the positive charge of Ca 2+ , Na + , and K + in the cement matrix and the negative charge of GO can cause agglomeration due to van der Waals forces, resulting in the formation of a weak zone within the cement-based matrix [33]. In another study conducted by Kei cui et al [19], which studied the impact of CNTs on the UHPC with two different dosages (0.09%, 0.15%), the results show great strength of the concrete, which contain CNTs with a large aspect ratio of 250-1500.…”
Section: Introductionmentioning
confidence: 99%